POSITIVE PSYCHOLOGY IN PRACTICE: FOSTERING MENTAL WELLNESS AMONG UNIVERSITY COUNSELORS - Yuan, Fang (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2023)
This research delves into the underexplored realm of college counselors’ mental health, shedding light on a crucial aspect of higher education. While major universities have made commendable strides in prioritizing mental health education for college students and accumulating substantial research in this domain, there exists a conspicuous dearth of attention directed towards the mental well-being of college counselors. This lacuna is especially concerning given the pivotal role counselors play in nurturing the emotional and psychological growth of students. This study addresses this gap by examining the mental health of college counselors, shedding light on the unique challenges and pressures they face in their roles. We investigate the turnover rate among counseling professionals, recognizing it as a tangible indicator of the strains and difficulties they encounter, often prompting some to opt out of the counseling profession altogether. Additionally, we delve into the experiences of counselors who choose to remain in their positions, unveiling the internal conflicts that can substantially dampen their work enthusiasm and overall life satisfaction. Furthermore, this research acknowledges the complex interplay of various factors in shaping the psychological well-being of college counselors. It is evident that these dedicated professionals, exposed to the emotional needs of students, inevitably grapple with their own psychological issues. Therefore, it is imperative to prioritize the mental health concerns of college counselors, recognizing that addressing these issues not only benefits the counselors themselves but also enhances their ability to provide effective support to students.